Kir3 channel ontogeny – the role of Gβγ subunits in channel assembly and trafficking - Zylbergold, Peter; Sleno, Rory; Khan, Shahriar M.; Jacobi, Ashley M.; Belhke, Mark A.; Hébert, Terence E. (Frontiers in Cellular Neuroscience, 2014)
The role of Gβγ subunits in Kir3 channel gating is well characterized. Here, we have studied the role of Gβγ dimers during their initial contact with Kir3 channels, prior to their insertion into the plasma membrane. We show that distinct Gβγ subunits play an important role in orchestrating and fine-tuning parts of the Kir3 channel life cycle. Gβ1γ2, apart from its role in channel opening that it shares with other Gβγ subunit combinations, may play a unique role in protecting maturing channels from degradation as they transit to the cell surface. Taken together, our data suggest that Gβ1γ2 prolongs the lifetime of the Kir3.1/Kir3.2 heterotetramer, although further studies would be required to shed more light on these early Gβγ effects on Kir3 maturation and trafficking.